Mentoring: An Evolving Relationship. (April 2017) - Block, Michelle; Florczak, Kristine L.
The column concerns itself with mentoring as an evolving relationship between mentor and mentee. The collegiate mentoring model, the transformational transcendence model, and the humanbecoming mentoring model are considered in light of a dialogue with mentors at a Midwest university and conclusions are drawn.